Athletic Speed Running Start Training Model For Student Athletes - Yobee, Darius; Fachrezzy, Fahmy; Setiakarnawijaya, Yasep (Jurnal Ilmu Sosial Mamangan, 2025)
The aim of this research is to produce and test the effectiveness of an athletic sprint start training model for student athletes. The research method used is a research and development method using the development model from Borg and Gall with the research design applied using a pretest-posttest control group design. The research stages consist of: 1) Research and Information Collecting, 2) Planning, 3) Developing the Preliminary from of Product, 4) Preliminary Field Testing, 5) Main Product Revision, 6) Main Field Testing, 7) Operational Product Revision, 8) Operational Product Testing, 9) Final Product Revision, 10) Desimination and Implementation. The subjects involved during the research were sports student athletes at Jakarta State University. The number of subjects during the small group test was 15 people and during the large group test there were 40 people. To test the effectiveness, the number of subjects involved was 32 people. The instruments in this research were interviews and questionnaires, as well as a sprint start skills test (squat start) for student athletes with a focus on the movement assessment process and also acceleration results recorded in units of time. The data analysis technique used in this research to test the effectiveness of the model is using paired sample t-test statistical analysis using the IBM SPSS Statistics 26 program. The results of the data analysis conclude that: 1) This athletic sprint start training model product for student athletes can be carried out. and applied in the sprint start training process,2) This athletic sprint start training model product for student athletes is effective for improving starting skills and increasing acceleration in sprinting for student athletes.